Shape controlled synthesis of concave octahedral Au@AuAg nanoparticles to improve their surface-enhanced Raman scattering performance. Issue 30 (6th July 2022) - Bi, Cuixia; Song, Yahui; Zhao, Hongyan; Liu, Guangqiang
Abstract : In this work, a seed mediated strategy has been proposed to design and fabricate uniform octahedral shaped gold@gold-silver nanoparticles (Au@AuAg NPs) with unique concave structure and an AuAg alloy shell. Abstract : In this work, a seed mediated strategy has been proposed to design and fabricate uniform octahedral shaped gold@gold-silver nanoparticles (Au@AuAg NPs) with unique concave structure and an AuAg alloy shell. The morphology and Au/Ag ratio of the Au@AuAg nanostructures can be delicately controlled by varying the concentration of reagents, namely the Au nanorod (NR) seeds, HAuCl4 and AgNO3 precursor. Besides, the investigation of the growth mechanism revealed that the morphology of the product also can be controlled by tuning the growth time. Furthermore, uniformly arranged assemblies of concave octahedral Au@AuAg NPs were prepared through a solvent evaporation self-assembly strategy and employed as surface-enhanced Raman scattering (SERS) substrates, effectively applied to the analysis of R6G for the examination of SERS performance. Satisfyingly, owing to the synergistic effect between the Au and Ag elements and concave structure, concave octahedral Au@AuAg NPs exhibit significantly higher SERS enhancement compared with traditional octahedral Au NPs, which have an enhancement factor of ∼1.3 × 10 7 and a detection limit as low as 10 −10 M. Meanwhile, the SERS substrate reveals an excellent uniformity and reproducibility of the SERS performance. This work opens a new avenue toward bimetallic NPs with concave structure, which have broad application prospects in optics, SERS detection and other fields.